Assessment of Community Pharmacist’s Practice and Patient Counselling Toward Acute Diarrhea Treatment in Khartoum Locality: A Simulated Patient Study - Hamadouk RM; Arbab AH; Yousef BA (Dove Medical Press, 2021)
Riham M Hamadouk,1 Ahmed H Arbab,2 Bashir A Yousef3 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 3Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Bashir A YousefDepartment of Pharmacology, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, Khartoum, 11111, SudanTel +249 155662037Fax +249 183780696Email bashiralsiddiq@gmail.comBackground: Acute diarrhea is one of the most common health problems globally as a minor ailment, it is widely managed by community pharmacists (CPs). Professional patient counseling provided in community pharmacies is essential to decide about acute diarrhea and avoid treatment failure properly.Objective: To assess CPs' history-taking practice, medication dispensing, and patient counseling in response to acute diarrhea in adults.Methods: A cross-sectional, covert simulated patient (SP) study was conducted in 235 community pharmacies in the Khartoum locality. Two scenarios were used, one scenario assesses afterwards compliance to treatment guidelines and patient counseling, and second scenario determines afterwards if pharmacists referred patients to medical consultation. Six final-year pharmacy students were involved as SPs. All encounters were audio-recorded by SP. Then the investigator filled the checklist that was intended to evaluate the overall practice of pharmacists.Results: As planned, 235 pharmacies were visited twice, resulting in a total of 470 visits (visit completion rate: 100%). In history taking, the most asked questions were the patient's age (89.8% for scenario 1 and 88.5% for scenario 2). Followed by the presence of blood in the stool (25.5% for scenario 1 and 28.1% for scenario 2). In scenario 1, loperamide was the most dispensed medication (81.3%), while oral rehydration solution (ORS) was dispensed in 0.9% of the visits. In counseling, verbal and written instructions were provided in 47.7% of the visits. Duration of medications was mentioned in 3.8%, advice about fluid intake was offered in 7.2% of the visits. In scenario 2, 17% of the pharmacists managed patient history well to refer patients to medical consultation, while 42.6% recommended referral after sufficient information was provided by the SP.Conclusion: CPs' practice in counseling toward acute diarrhea was poor; referral to medical consultation was below expectation. The current CPs dispensing practices need improvement; thus, professional education should be encouraged.Keywords: acute diarrhea, community pharmacists, simulated patient, medical consultation